Evaluation of fosfomycin activity against uropathogens in a fosfomycin-naive population in South India: a prospective study. (May 2013) - Sahni, Rani Diana; Balaji, Veeraraghavan; Varghese, Rosemol; John, James; Tansarli, Giannoula S; Falagas, Matthew E
Aim: The aim was to evaluate the in vitro activity of fosfomycin against common uropathogens in a fosfomycin-naive population in India.Methods: The authors prospectively collected and tested all consecutive isolates of Escherichia coli and Enterococcus spp. from urine samples between December 2009 and April 2010.Results: A total of 3141 isolates were included in the study, 2416 E. coli and 725 Enterococcus spp. Fosfomycin was the most active antibiotic against both pathogens with an overall susceptibility of 83 and 99% for E. coli and Enterococcus spp, respectively. Among E. coli, 47.6% of the isolates were extended-spectrum β-lactamase producing, of which 81% were susceptible to fosfomycin, while 51.5% were multidrug resistant, with 75.7% of this portion being susceptible to fosfomycin.Conclusion: Fosfomycin exhibits good in vitro activity against both the uropathogens tested. Therefore, it might be considered as a treatment option for urinary tract infections in India; however, clinical trials should first reinforce the in vitro findings.